Validated High Performance Liquid Chromatographic Method for Estimation of Nisoldipine from Matrix Type Transdermal Films: Application to Ex vivo Skin Permeability Studies - Gayatri, P. (Asian Journal of Pharmaceutics (AJP), 2017)
Context: Assessment of nisoldipine (NSP) skin flux using validated high-performance liquid chromatographic (HPLC) method. Aim: A validated HPLC method was developed for estimation of NSP in skin permeated samples from matrix type transdermal films. Materials and Methods: Chromatographic separation was done using Phenomenex Luna C18 column (150 mm Ã— 4.6 mm i.d. 5 Î¼m) employing acetonitrile:water:methanol (40:35:25 v/v) as the mobile phase. Settings and Design: The calibration solutions were prepared in the linearity range of 0.250-50 Î¼g/mL. The flow rate was maintained at 0.8 mL/min at 25Â°C. 10 Î¼L samples were injected and were monitored using photodiode array detector at a wavelength of 275 nm. Results: The limit of detection and limit of quantification for NSP were recorded as 0.125 Î¼g/mL and 0.150 Î¼g/mL, respectively. The correlation coefficient (r2) values for intraday and interday were >0.998 and % relative standard deviation values were <10%. Conclusions: The method was validated as per International Conference on Harmonization guidelines, found to be simple, sensitive, cost effective and was successfully used for ex vivo skin permeation studies of NSP from matrix type transdermal films.